CHRISTIAN EDUCATION TEACHER AS FACILITATOR BASED ON CONSTRUCTIVE SANCTIONS: A CASE STUDY AT JUNIOR HIGH SCHOOL 7 PALANGKA RAYA - Nanda Monica (STKIP PGRI Situbondo, 2023)
The purpose of this study is to find out the extent of the experience and perception of Christian Religious Education Education teachers as facilitators in providing constructive sanctions against students at SMP Negeri 7 Palangka Raya. The research method I use through qualitative research with interview techniques. I, first made an observation of a school close to where I lived. Then, interview the subjects of the study. The results of the subject narrative I transcribed then made into factual solids to form the theme of the discussion. My findings show that junior high schools in Palangka Raya have so far implemented constructive indiscipline for a long time. Constructive because as far as I know, not indiscipline is stigmatized as something destructive.